Pre-operative methicillin resistant Staphylococcus aureus results do not predict surgical site infections in children undergoing varus derotational osteotomy. Issue 26 (26th June 2020) - Nazareth, Alexander; Bains, Sukhraj S.; Andras, Lindsay M.; Goldstein, Rachel Y.; Kay, Robert M.
Abstract : Abstract: Literature regarding the value of pre-operative nasal methicillin resistant S taphylococcus aureus (MRSA) swabs to predict surgical site infections (SSIs) in children undergoing lower extremity surgery is limited. The purpose of our study was to determine if pre-operative nasal MRSA swab results were predictive of SSI development in children undergoing a femoral varus derotational osteotomy (VDRO). Patients who underwent VDRO between 2004–2016 were reviewed to determine pre-operative MRSA colonization rates and SSI devolvement rates. Patients with less than 1 year of follow-up, previous history of infections, or absent pre-operative MRSA swab were excluded. SSI rates of patients with negative MRSA and positive MRSA swab result were compared using the Fisher exact test. Aside from contact isolation precautions, no other changes in treatment were made during inpatient hospital course based on positive pre-operative nasal MRSA swab results. 247 patients met the inclusion criteria (mean age: 9.3 ± 3.6 years, 62% male). There were 242 (98%) patients with a negative MRSA swab and 5 (2%) patients with a positive MRSA swab. Out of the 242 patients with a negative MRSA swab, 4 developed an SSI. Of the patients with positive MRSA swab results, 0% (0/5) developed an SSI compared to 1.7% (4/242) of negative MRSA swab results who developed an SSI. Results indicated no significant difference in SSI development rates between the groups ( P = 1.00). In this series of children undergoing VDRO surgery, the results of a pre-operative MRSA nasal swab had no relationship to SSI incidence and no impact on clinical patient care. Pre-operative MRSA nasal swabs appear to be of limited benefit for routine pre-operative screening in this patient population. Level III, retrospective comparative